Analisis Prosedur Penggantian Arrester pada Jaringan Distribusi PT. PLN (PERSERO) UP3 Cikupa - Dendi Agustian; Melti Septiani; Romdoni, Sohip; Anzhari, Hafiz; Bragi Muslim, Aldi; Didik Aribowo (SURYA TEKNIKA, 2024)
The electricity distribution network is the backbone of energy supply from power plants to consumers. One important component of the distribution network is the arrester, which serves to protect equipment from sudden voltage surges, such as those caused by lightning strikes. Arresters are designed to withstand overvoltage and protect transformers and other sensitive components from damage. This research uses a case study method with a descriptive qualitative approach. Data were collected through interviews with technicians involved in network maintenance and field inspections of the condition of arresters in the distribution network of PT. PLN (Persero) UP3 Cikupa. The research findings indicate that several arresters in the distribution network of PT. PLN (Persero) UP3 Cikupa receive voltages that do not meet technical specifications, leading to voltage leakage. Based on the research results, it can be concluded that regular replacement of arresters is necessary to maintain the reliability of the electricity distribution network. Voltage leakage caused by discrepancies between incoming voltage and the technical specifications of the arresters has the potential to cause damage to network equipment, particularly transformers.